PERAN UNIT DIKYASA POLRESTABES BANDUNG DALAM MENGURANGI PELANGGARAN LALU LINTAS PADA KALANGAN PELAJAR MELALUI PROGRAM POLICE GOES TO SCHOOL - BISMA WIRA PUTRA (Advances in Police Science Research Journal, 2020)
ABSTRACT The background to this problem arises because of increased traffic violations among students in the Bandung City area. Therefore, the role of the unit in providing community education and then through the Police Goes To School program is very important to reduce the occurrence of traffic violations committed by students in the Bandung police jurisdiction. The purpose of this study is to want to know the role of units in Bandung police service through the Police Goes To School program in reducing traffic violations among students, want to find out the factors that influence the implementation of community education and then through the Police Goes To School program in Bandung police in reducing past violations traffic to students, and want to find out how to increase the role of the Bandung police polytechnic unit in reducing traffic violations among students through the Police Goes To School program. This research was conducted with a qualitative approach that seeks to obtain a picture of a phenomenon in more depth by using field research methods and data collection techniques by interviewing, observing, and using document studies. In this study also uses management theory and communication theory as a knife in analyzing the problems that occur in the field. The results showed that the implementation of the Police Goes To School program for students at Bandung police station was in accordance with the plan, but the plan was not effective enough because the method used was in the form of counseling to schools that only received an average visit once in five months. And there are obstacles in the form of quantity and quality of personnel as well as inadequate budget and infrastructure. As for suggestions from researchers, Bandung police can provide vocational education and then to its members, increase counseling schedules to schools, provide counseling not only for students but also for students' parents, and participate in working with related institutions such as the education office.